Biodegradability and Cavitation Erosion Behavior of Some Zinc Alloys from the System ZnCuMg - Brandusa Ghiban; Aurora Antoniac; Ilare Bordeasu; Iulian Antoniac; Gabriela Petre; Julietta V. Rau; Dorin Bordeasu; Lavinia Madalina Micu (Metals)
This paper presents experimental results regarding the development of new alloys from the binary ZnCu and ternary ZnCuMg systems. The alloys had controlled chemical compositions and were annealed at 300 °C and 400 °C, with holding times of 5 h and 10 h, followed by air cooling. Mechanical properties (tensile strength, yield strength, elongation, and elastic modulus) were determined. Structural analysis conducted after different heat treatments revealed that homogenization transforms the dendritic structure into a granular structure with intergranular eutectic presence. Biodegradation behavior showed that the ternary alloy exhibits higher degradation rates than the binary alloy. Applying the homogenization heat treatment has a good influence on the binary alloy only, not on the ternary alloy. Our research shows that that the complex alloying of zinc with copper and magnesium may improve cavitation behavior, doubling both the MDEmax parameter and cavitation resistance expressed by Rcav.